2018
DOI: 10.1039/c7sc05371a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry as an emerging tool for molecular synthesis: what can it offer?

Abstract: Mechanochemistry is becoming more widespread as a technique for molecular synthesis with new mechanochemical reactions being discovered at increasing frequency. This perspective explores what more it can offer, aside from the clear benefit of reduced solvent consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
471
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 759 publications
(478 citation statements)
references
References 120 publications
1
471
0
6
Order By: Relevance
“…Furthermore, it has been shown that, for certain examples, significant advantages over solution chemistry can be obtained, such as a decrease in reaction time or improvement in selectivity 1k. There are also examples where the use of mechanochemistry can alter reactivity, resulting in different products when compared to solution or liquid assisted grinding (LAG) 1k,1l. For example, previous work in our group has shown the use of LAG to control the selectivity of mechanochemical fluorination (Scheme 1 a) 3.…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that, for certain examples, significant advantages over solution chemistry can be obtained, such as a decrease in reaction time or improvement in selectivity 1k. There are also examples where the use of mechanochemistry can alter reactivity, resulting in different products when compared to solution or liquid assisted grinding (LAG) 1k,1l. For example, previous work in our group has shown the use of LAG to control the selectivity of mechanochemical fluorination (Scheme 1 a) 3.…”
mentioning
confidence: 99%
“…[1][2][3][4] In the last few decades, the number of applications has rapidly grown and now covers many fieldsi ncluding organic, [5][6][7][8][9][10] inorganic, [11] and chemoenzymatic [12] synthesis, supramolecular chemistry, [13,14] pharmacy, [15] andm aterials chemistry. [3,18,19] These advantages can be attributed to efficient surfacec ontact, high local concentration, and temperature. [3,18,19] These advantages can be attributed to efficient surfacec ontact, high local concentration, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Abgesehen davon, dass sie als nachhaltigere Alternative zur Einleitung chemischer Umwandlungen anerkannt wurde, [12] hat Mechanochemie durch Kugelmahlen die Synthese von Substanzen ermçglicht, die schwer oder gar nicht durch klassische Synthese zugänglich sind. [14,15] Obwohl Mechanochemie die chemischen und physikochemischen ¾nderungen einer Substanz in allen Aggregatzuständen umfasst, behandeln die meisten Beispiele mechanochemischer Umwandlungen durch Kugelmahlen die Reaktionen von Festkçrpern oder Flüssigkeiten. [14,15] Obwohl Mechanochemie die chemischen und physikochemischen ¾nderungen einer Substanz in allen Aggregatzuständen umfasst, behandeln die meisten Beispiele mechanochemischer Umwandlungen durch Kugelmahlen die Reaktionen von Festkçrpern oder Flüssigkeiten.…”
Section: Introductionunclassified